2016
DOI: 10.4103/0970-4388.186749
|View full text |Cite
|
Sign up to set email alerts
|

Management of grossly decayed primary anteriors using various intracanal post systems: A clinical study

Abstract: Both glass post and polyethylene post proved to be effective. Glass post showed the maximum retention and marginal adaptation followed by polyethylene post. Thus, it appears to be of potential interest for use especially in clinical pediatric dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The use of both glass and polyethylene FRC posts to restore grossly destroyed primary incisors is a challengeable treatment option. Mehra et al , reported one year data of 45 grossly decayed primary anterior teeth, which were endodontically treated and fiber posts (glass and polyethylene) placed in the canals ( 23 ). After an interval of 12 months, significant difference ( p <0.05) was observed between different FRC posts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of both glass and polyethylene FRC posts to restore grossly destroyed primary incisors is a challengeable treatment option. Mehra et al , reported one year data of 45 grossly decayed primary anterior teeth, which were endodontically treated and fiber posts (glass and polyethylene) placed in the canals ( 23 ). After an interval of 12 months, significant difference ( p <0.05) was observed between different FRC posts.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, marginal discoloration comparison was done after 12 months, and 20% of the teeth exhibited marginal discoloration in polyethylene FRC post group, while only 13.3% in glass FRC post group. Authors stated that durability of glass FRC posts may be attributed to the individual fiber quantity, composition of resin matrix (epoxy resin with approximately 65 vol% glass fiber content) and the adequate adhesion of the fibers to the polymer matrix ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…The glass fiber post has a modulus of elasticity (54 GPa) close to that in dentin (approximately 18 GPa; Lamichhane et al, 2014). It was lute with flowable composite in Group A (glass fiber post) as described in previous in vivo (Mehra et al, 2016; Sharaf, 2002; Subramaniam et al, 2008; Vafaei et al, 2016) and in vitro (Baghalian, Ranjpour, Hooshmand, Herman, & Ebrahimi, 2014; Memarpour et al, 2013; Sharaf, 2002) studies which had reported high success rates in this technique.…”
Section: The Discussionmentioning
confidence: 99%
“…Mehra et al (2016) reported a 93.33% success rate in glass fiber post group after 12 months post‐treatment. The failures in their study had happened because of biting on hard food.…”
Section: The Discussionmentioning
confidence: 99%
“…This is due to the small size of the crown, relatively large pulp chambers, and the age of the child. The remaining inadequate sound tooth structure renders restorations more prone to fractures [6] Over the last few decades, various treatment strategies have been introduced such as, crowns for the coronal restorations, made of polycarbonate, cellulose strip crowns, art glass crowns, as well as veneered stainless steel crowns. Although it was found that in cases with severe carious loss of tooth structure, these restorations could not successfully withstand the occlusal forces [7].…”
Section: Introductionmentioning
confidence: 99%